Europe recast: a history of European Union - Dinan, Desmond (Basingstoke, 2004)
"Europe Recast tells the story of European integration from its modern origins in the 1940s to the challenges of the new century. Organized chronologically with each chapter broadly covering a decade, a thematic introduction and concluding chapter draw out key issues and themes and provide the author's own distinctive interpretation. Written by a leading authority, and highly successful textbook author, in a clear, entertaining and accessible style, the book is sure to become the leading text for all students of the history and evolution of the European Union."